2018
DOI: 10.1021/acs.iecr.8b04341
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Coaxial Spinneret in Taylor Cone and Morphology of Core–Shell Fibers

Abstract: This paper reports on the roles of three coaxial spinnerets with different electric field distributions, including retracting spinneret, flat spinneret, and protruding spinneret in the Taylor cone, jet motion, and resultant core−shell fibers. The Taylor cone, jet motion, and the morphology and internal structure of resultant core−shell fibers for these three abovementioned spinnerets are systematically studied. The results show that the Taylor cone, jet motion, and core−shell fiber morphology are influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In the coaxial method, two needles are coaxially placed together for two different polymeric solutions. The core material, which was pumped through the inner needle, whereas the shell material was pumped from the outer needle of the coaxial spinneret [41]. The main parameter for this method is that the shell material is likely to be in the electrospinnable polymer solution, whereas the core material is likely to be a drug solution or other non-spinnable material.…”
Section: Fabrication Of Epnfsmentioning
confidence: 99%
“…In the coaxial method, two needles are coaxially placed together for two different polymeric solutions. The core material, which was pumped through the inner needle, whereas the shell material was pumped from the outer needle of the coaxial spinneret [41]. The main parameter for this method is that the shell material is likely to be in the electrospinnable polymer solution, whereas the core material is likely to be a drug solution or other non-spinnable material.…”
Section: Fabrication Of Epnfsmentioning
confidence: 99%
“…The Taylor cone is influenced by a multitude of factors—flow rate [ 32 , 33 , 34 ], conductivity [ 32 ], nozzle diameter [ 32 ] and geometry (in coaxial spinning) [ 35 ], viscosity [ 32 ], polymer used [ 36 ], surface charge [ 37 ], charge density [ 38 ], applied voltage [ 33 , 39 ], and solvent [ 40 ]. Additionally, an interesting paper has investigated the effect of different setup orientations on the half-angle of the Taylor cone.…”
Section: State Of the Art—impact Of Apparatus Orientation In Electmentioning
confidence: 99%
“…Thus, the jet initiation and resulting fiber morphology depend heavily on the electric field strength around the spinneret and in the electrospinning region that is mainly governed by the applied voltage and the spinneret shape 15 . Substantial research efforts have shown that the uniform electric field distribution can produce thinner and more uniform fibers 16,17 . At present, the strategies to improve the electric field distribution are mainly divided into three categories, containing the development of spinnerets, 18 the design of collectors, 19 and the addition of auxiliary electrodes 20 …”
Section: Introductionmentioning
confidence: 99%
“…15 Substantial research efforts have shown that the uniform electric field distribution can produce thinner and more uniform fibers. 16,17 At present, the strategies to improve the electric field distribution are mainly divided into three categories, containing the development of spinnerets, 18 the design of collectors, 19 and the addition of auxiliary electrodes. 20 Zhou et al 21 employed a flat plastic spinneret with a custom-made-three-hole instead of the conventional needles in the electrospinning system.…”
mentioning
confidence: 99%